ANALISIS MEDIA PEMBELAJARAN CANVA PADA KEMAMPUAN MENULIS DI SEKOLAH DASAR: (Analysis of Canva Learning Media on Writing Skills in Elementary School) - Mustika Putriani; Vevy Liansari (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2026)
This research is motivated by the importance of using digital learning media in improving the writing skills of elementary school students. One media that can be used is Canva, which provides various attractive visual design features to support Indonesian language learning. This study aims to determine students' responses to the use of Canva learning media on writing skills at SDN 3 Gedompol. This study used a qualitative method with a phenomenological approach. The research subjects consisted of one fourth-grade teacher and eight fourth-grade students. The research subjects were limited because the phenomenological approach was used to gain in-depth knowledge of their experiences in implementing Canva. Data collection techniques were carried out through observation, in-depth interviews, and documentation. Data analysis was carried out through the stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate that the use of Canva learning media has a positive impact on writing learning. Teachers are able to implement Canva well, so that learning becomes more interactive and systematic. Students show positive responses, such as increased attention, motivation, participation, and creativity in writing. In addition, Canva helps students in finding ideas, developing writing, and producing better written works. Thus, Canva learning media can be an effective alternative to support the development of elementary school students' writing skills. However, despite its positive impacts, there are also challenges in its implementation, necessitating appropriate solutions to address these challenges.